Management of solid organ injury in patient of blunt abdominal trauma - Baldiwala, Aafrin S.; Lad, Vipul C. (International Surgery Journal, 2021)
Background: In this ongoing era of 21st century, trauma is the leading cause of death in individuals between age 1 and 44. In trauma, also road traffic accidents (RTAs) are the major cause of death. Blunt abdominal trauma is a frequent emergency and is associated with significant morbidity and mortality. Methods: A prospective analysis of 50 patients of blunt abdominal trauma admitted in SMIMER hospital Surat within a span of 12 months was done. Unstable patients with initial resuscitation underwent focused assessment sonography for trauma (FAST). Failed resuscitation with free fluid in abdomen confirmed by FAST immediately shifted to operation theatre for laparotomy and proceed. Hemodynamically stable patients underwent computerized tomography of abdomen. Results: Most of the patients in our study were in the age group of 21-45 years with M:F ratio of 4:1. RTAs (62%) was the most common mechanism of injury. Spleen (38%) was the commonest organ injured and the most common surgery performed was splenectomy. In total non-operative management (NOM) was done in 58% of cases and surgical management was done in 42% of cases. Conclusions: Appropriate patient selection, early diagnosis and repeated clinical examination and use of appropriate investigations forms the key in management of blunt abdominal trauma. To conclude, initial resuscitation measures and correct diagnosis forms the most vital part of blunt abdominal trauma management.